THE DYNAMIC MODEL OF URBAN DEVELOPMENT AND ENVIRONMENT CARRYING CAPACITY IN ISLAND CITY BY DYNAMIC SYSTEM APPROACH (CASE STUDY: TARAKAN CITY) - Wibisono, Ashari
The trend of expansively and sprawl development of urban areas basically leads to the unsustainability of the urban environment indicated by decreasing in environmental carrying capacity. The same case happened in the context of the Island City, Tarakan City is one of the island cities in Indonesia that according to Government Regulation Number 13 Year 2017 The National Spatial Plan, it is designated as the National Activity Center which acts as a center for trading and services and as sea and air transportation services center. Having that role the attractiveness of Tarakan city is increasing and attracting outsiders to migrate to Tarakan City, causing an increase of land and raw water need indicating decrease of future environmental carrying capacity. To anticipate the exceeding of environmental carrying capacity, policy scenario was developed to minimize urban developmental problems and environmental carrying capacity in the future. This research conducted System Dynamic model that shows the effects occur when the population increases, the improving of built up and economical area will impact on environmental carrying capacity. Based on the population and economy growth impact on environmental carrying capacity simulation result shows that land carrying capacity is 1.07 and water carrying capacity is 1.01, these explain that overall the environmental carrying capacity of Tarakan city at the end of the simulation is conditionally sustained.